The development of the informational and communication subject environment for the future mathematics teacher - Madina Jamankarayeva, Roza Kadirbayeva, Aldanazar Amirbekuly,; Issabek, Barshagul; Ibashova, Almira (Opción, 2019)
The article describes the relevance of the formation of professional competence at the future mathematics teacher through the development of ICSE in the school course of mathematics via comparative qualitative research methods. As a result, the majority of students of the group voluntarily expressed a desire to work on their own work and efficiently developed elective courses of ICSE in the school course of mathematics. In conclusion, the suggested informational and pedagogical technology of the formation of professional competence at future mathematics teachers through the development of ICSE can be called a breakthrough for the following reasons.